Anti-cytokines and cytokines in the treatment of rheumatoid arthritis. - Taylor, P (2003)
The treatment approach to rheumatoid arthritis has undergone a major evolutionary change in recent years in part as a consequence of growing appreciation of the severity of this condition and in part due to very considerable progress in understanding the important role of cytokines in the immunopathogenesis of this disease. The major focus of this review is on the rationale for targeting TNFalpha and IL-1 in rheumatoid arthritis and the results of clinical studies designed to assess the validity of this therapeutic approach. Recently published studies confirm that the long term use of a several biological agents targeting TNFalpha give rise to sustained improvements in symptoms and signs of rheumatoid disease and, furthermore, that TNFalpha blockade protects joints from structural damage. Although these drugs are well tolerated and have a good overall safety profile, pitfalls to the use of anti-TNFalpha agents apparent with increasing clinical experience include rare cases of tuberculosis. The mechanism of action of anti-TNFalpha therapy is discussed. Clinical trials of interleukin-1 receptor antagonist show relatively modest anti-inflammatory efficacy and an effect on X-ray indicative of retardation of joint damage. Other pro-inflammatory cytokines representing potential therapeutic targets include interferon-beta, interferon-alpha, IL-6, IL-15, IL-17 and IL-18. I will consider preliminary data, where available, arising from clinical trials designed to inhibit the activity of such molecules. In this review I will also discuss the rationale and preliminary data for other potential therapeutic strategies designed to augment the activity of anti-inflammatory cytokines such as IL-4, IL-10, and IL-11 in rheumatoid disease.